(untitled) (Quinto Sol, 2010)
Productive possibilities in Patagonia region, from the point of view of natural resources, were based up on the cattle range (mainly sheep) as well as a lightly agriculture. Because of that, economic growing was planned as “growing for outside”, as it was carried out and considered for the national development in the end of 19th century and also the beginning of the 20th one. Nevertheless, there was an exception: that was the frustrated project of patagonian development thought and written by Ezequiel Ramos Mexía, Ministry of Public Works of President Figueroa Alcorta. It was set up in the promotion law of National Territories N° 5.559 of 1908. The ministry, son and grandson of great land owners of the pampean region, province of Buenos Aires, had a wide angle of thinking about economic development affairs. In this respect, Patagonia looks to him as a suitable territory to improve out a process of development which can go further than a country based on the simple production of agrarian commodities, as it was in general, the policy followed in those times.